Turning brain MRI into diagnostic PET: 15O-water PET CBF synthesis from multi-contrast MRI via attention-based encoder–decoder networks - Hussein, Ramy; Shin, David; Zhao, Moss Y.; Guo, Jia; Davidzon, Guido; Steinberg, Gary; Moseley, Michael; Zaharchuk, Greg (Medical image analysis, 2024)
Accurate quantification of cerebral blood flow (CBF) is essential for the diagnosis and assessment of a wide range of neurological diseases. Positron emission tomography (PET) with radiolabeled water (15O-water) is the gold-standard for the measurement of CBF in humans, however, it is not widely available due to its prohibitive costs and the use of short-lived radiopharmaceutical tracers that require onsite cyclotron production. Magnetic resonance imaging (MRI), in contrast, is more accessible and does not involve ionizing radiation. This study presents a convolutional encoder–decoder network with attention mechanisms to predict the gold-standard 15O-water PET CBF from multi-contrast MRI scans, thus eliminating the need for radioactive tracers. The model was trained and validated using 5-fold cross-validation in a group of 126 subjects consisting of healthy controls and cerebrovascular disease patients, all of whom underwent simultaneous 15O-water PET/MRI. The results demonstrate that the model can successfully synthesize high-quality PET CBF measurements (with an average SSIM of 0.924 and PSNR of 38.8 dB) and is more accurate compared to concurrent and previous PET synthesis methods. We also demonstrate the clinical significance of the proposed algorithm by evaluating the agreement for identifying the vascular territories with impaired CBF. Such methods may enable more widespread and accurate CBF evaluation in larger cohorts who cannot undergo PET imaging due to radiation concerns, lack of access, or logistic challenges. •Accurate CBF quantification is crucial for cerebrovascular disease diagnosis•15O-water Positron emission tomography (PET) is the gold-standard for CBF measurement•Attention-based network transforms multi-contrast MRI into high-quality PET CBF maps•Experiments on two cohorts demonstrate efficiency and reliability of proposed method•Quantitative and qualitative results show clinical significance of proposed method•Brain regions with abnormally low CBF are successfully detected in synthetic PET CBFs